The efficiency in the treatment of effluent bullets industry with sludge modification in anaerobic - Neckel, Alcindo (2016)
This study aimed to attempt to resolve the deficiency of a candy industry to treat its effluent with the replacement of the up flow anaerobic sludge for their improved sustainability. This is a case study where proposes two alternative sludge with different characteristics for pH and COD concentration of the effluent from the reactor has characteristics that facilitate the remainder of the process. After the analysis it can be concluded that the sludge 1 bullet factory, showed the best performance to solve the problem.